Information computing and applications second international conference, ICICA 2011, Qinhuangdao, China, October 28-31, 2011. Proceedings - Liu, Baoxiang; Chai, Chunlai (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the Second International Conference on Information Computing and Applications, ICICA 2010, held in Qinhuangdao, China, in October 2011. The 97 papers presented were carefully reviewed and selected from numerous submissions. They are organized in topical sections on computational economics and finance, computational statistics, mobile computing and applications, social networking and computing, intelligent computing and applications, internet and Web computing, paralelle and distributed computing, and system simulation and computing.